Mechanisms of Acupuncture in the Regulation of Oxidative Stress in Treating Ischemic Stroke. (29th October 2020) - Su, Xin-Tong; Wang, Lu; Ma, Si-Ming; Cao, Yan; Yang, Na-Na; Lin, Lu-Lu; Fisher, Marc; Yang, Jing-Wen; Liu, Cun-Zhi
Abstract : Ischemic stroke is the major type of cerebrovascular disease usually resulting in death or disability among the aging population globally. Oxidative stress has been closely linked with ischemic stroke. Disequilibrium between excessive production of reactive oxygen species (ROS) and inherent antioxidant capacity leads to subsequent oxidative damage in the pathological progression of ischemic brain injury. Acupuncture has been applied widely in treating cerebrovascular diseases from time immemorial in China. This review mainly lays stress on the evidence to illuminate the possible mechanisms of acupuncture therapy in treating ischemic stroke through regulating oxidative stress. We found that by regulating a battery of molecular signaling pathways involved in redox modulation, acupuncture not only activates the inherent antioxidant enzyme system but also inhibits the excessive generation of ROS. Acupuncture therapy possesses the potential in alleviating oxidative stress caused by cerebral ischemia, which may be linked with the neuroprotective effect of acupuncture.